Monte Carlo Simulation to increase the efficiency of Gas Distribution in Padang City - Zulfitri Yani; Nurmaliana Pohan; Devi Gusmita; Eva Rianti (Universitas Islam Kuantan Singingi, 2023)
PT. Cahaya Hermes Indo Abadi is one of the largest non-subsidized gas distributors in the city of Padang. Gas is a necessity in society. It is necessary to pay attention to the availability of gas to meet consumer needs, the state of gas stocks can affect the level of sales revenue. Sales relate to consumer desires for goods and services that they want to fulfill. Increasing the amount of gas demand can generate a large income. In predicting gas needs, a method is needed that is able to overcome society's gas needs. One of the methods used in this research is the Monte Carlo Method. This method is able to overcome further gas needs so data is needed to overcome this problem. The data used is 12 Kg non-subsidized gas sales data for three years, namely Gas Sales Data for 2021, 2022, and Gas Sales Data for 2023. The level of prediction accuracy in 2022 is 86.9% and in 2023 the accuracy is 86.6%. Based on the gas distribution simulation that has been carried out, the average is 86.75%. By obtaining a greater level of accuracy, this method is suitable for use and implementation in predicting future gas demand, making it easier for companies to make decisions in the future.